When Cultures Fail: Postmortem Decoy Receptor 3 (DcR3) as a Marker of Antemortem Sepsis. Issue 1 (March 2019) - Thompson, Katrina; Connor, Joseph
Introduction: Decoy receptor 3 (DcR3) has shown utility as a reliable surrogate marker. Levels of DcR3 in the serum increase and remain elevated in several disease states including cancer and sepsis. In inflammatory conditions, DcR3 is upregulated in inflammatory cells to suppress exponential immune propagation. The use of DcR3 as an indication of sepsis has been documented in the antemortem setting, but its use in the postmortem setting is unknown. The purpose of this study is to evaluate postmortem DcR3 as a marker of antemortem sepsis. Methods: A retrospective investigation was performed to identify patients whose primary cause of death fell into one of four cohorts (control, cancer, culture-positive sepsis, and suspected culture-negative sepsis). Serum was obtained and tested by a commercially available enzyme-linked immunosorbent assay to quantify DcR3 levels. Results: Twenty-five of 47 samples contained detectable levels of DcR3 (average 0.75 ± 0.3 ng/mL). Comparing culture-positive sepsis to the control cohort at a cutoff value of 0.26 ng/mL, DcR3 positivity showed a sensitivity of 64% and a specificity of 73%. Compared to each other, patients with cancer had similar values to those with culture-positive sepsis (P = .90). Time of specimen collection had a negative role in detection and quantification (P = .038). Discussion: Several studies have shown DcR3 may be a viable antemortem biomarker of sepsis, but its use in postmortem sepsis testing has not been adequately investigated. This study shows that in postmortem testing, DcR3 shows less sensitivity and specificity with a relatively short window for proper testing.